Animal Stories for 5 year olds - Wallis;Diz (London Macmillan Children's Books, 2017)
Animal Stories for 5 Year Olds is rich and varied selection of heart-warming animal stories by some of the very best writers for children. Perfect for reading alone or reading aloud - and for dipping into time and time again. With stories from Dick King-Smith, Joyce Lankester-Brisley, Dorothy Edwards, Margaret Mahy and many more, this book will provide hours of fantastic fun